Sexual harassment: the legal issues in Malaysia / Nooraishah Azis and Aliff Marzuki Mahmud Marzoki - Azis, Nooraishah; Mahmud Marzoki, Aliff Marzuki (2008)
This research is about the issue of sexual harassment and the legal issues in Malaysia. In 1999 the Minister of Human Resource had introduced the Code of Practice and Eradication of Sexual Harassment in the Workplace. The existence of this Code was supposed to be the solution to this problem. However, since it is merely a guideline, it does not have any mandatory effects. There are other laws in Malaysia which governs sexual harassment. However, these laws are not sufficient in curbing the rising issue of sexual harassment in our country. The lack of laws in Malaysia causes the victims to have no legal redress. Thus many cases go unreported. Among others, this research will include not only the legal aspects of sexual harassment but also the impact of this problem from a social perspective. The level of social awareness among the public is not encouraging. Therefore, recommendations on how to properly address this issue will also be included. In conclusion, legislate the Code to an Act will be a very helpful step in curbing sexual harassment.